2023
DOI: 10.3390/economies11060161
|View full text |Cite
|
Sign up to set email alerts
|

Youth Entrepreneurship in Germany: Empirical Evidence on the How, the Why, the How Many, the Who and the When

Abstract: Youth entrepreneurship is an increasingly prominent aspect of entrepreneurship support policies, but there is surprisingly little relevant research-based empirical evidence. This research gap is particularly noticeable when it comes to the personal and contextual factors that steer young people’s decision to start a business. Using statistically representative survey data from the Global Entrepreneurship Monitor for Germany, we apply logit regressions to determine the influence of 10 independent variables on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…In this regard, the study's findings are somewhat comparable to those of Wu Yanhua. An article published in 2023 by Rolf Sternberg and David Breitenbach researched the entrepreneurial conduct of young Germans and validated the connection between age and entrepreneurial selection [5]. They concluded that: Compared to older individuals, young adults exhibit a lower propensity to initiate a business venture due to an absence of sufficient social experience, prior failure, and financial resources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this regard, the study's findings are somewhat comparable to those of Wu Yanhua. An article published in 2023 by Rolf Sternberg and David Breitenbach researched the entrepreneurial conduct of young Germans and validated the connection between age and entrepreneurial selection [5]. They concluded that: Compared to older individuals, young adults exhibit a lower propensity to initiate a business venture due to an absence of sufficient social experience, prior failure, and financial resources.…”
Section: Literature Reviewmentioning
confidence: 99%